Multiscale characterization of pathological bone tissue. Issue 2 (7th September 2021) - Eren, E. Deniz; Nijhuis, Wouter H.; van der Weel, Freek; Dede Eren, Aysegul; Ansari, Sana; Bomans, Paul H.H.; Friedrich, Heiner; Sakkers, Ralph J.; Weinans, Harrie; de With, Gijsbertus
ABSTRACT: Bone is a complex natural material with a complex hierarchical multiscale organization, crucial to perform its functions. Ultrastructural analysis of bone is crucial for our understanding of cell to cell communication, the healthy or pathological composition of bone tissue, and its three‐dimensional (3D) organization. A variety of techniques has been used to analyze bone tissue. This article describes a combined approach of optical, scanning electron, and transmission electron microscopy for the ultrastructural analysis of bone from the nanoscale to the macroscale, as illustrated by two pathological bone tissues. By following a top‐down approach to investigate the multiscale organization of pathological bones, quantitative estimates were made in terms of calcium content, nearest neighbor distances of osteocytes, canaliculi diameter, ordering, and D‐spacing of the collagen fibrils, and the orientation of intrafibrillar minerals which enable us to observe the fine structural details. We identify and discuss a series of two‐dimensional (2D) and 3D imaging techniques that can be used to characterize bone tissue. By doing so we demonstrate that, while 2D imaging techniques provide comparable information from pathological bone tissues, significantly different structural details are observed upon analyzing the pathological bone tissues in 3D. Finally, particular attention is paid to sample preparation for and quantitative processing of data from electron microscopic analysis. Abstract : Multiscale characterization of pathological bone tissues.